Redesign of Zinc Polycarboxylate Dental Cement - Saad B. H. Farid (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The formulations and the properties of the Zinc Polycarboxylate Dental Cements are reviewed then new cements of this type are prepared with modified solid part of the cement. High silica glass powder with different particle sizes is prepared and added with different weight percentages to the zinc oxide. The liquid part of the prepared cements was merely 44% concentration of the polyacrylic acid. Accordingly, the usual and expensive additives to the liquid and solid part of the cement are eliminated. The working and setting times, compressive strength, flexural strength and modulus are measured according to ADA specifications. The formulated cement has long working times without much lengthening of the setting times. In addition, the mechanical properties have noticeably improved as compared with the original cements